Tropical Pathology Research in the department of Madre de Dios - Cornejo Donayre, Alberto (1960)
Studying tropical deseases in the Department of Madre de Dios, we had the opportunity to colect some snakes there and in the city of Quincemil wich is situaded in the jungle of the Department of Cuzco, bordering with Madre de Dios. The snakes where studied by Dr. Jehan Vellard from the Museo de Historia Natural Javier Prado de la Universidad Nacional Mayor de San Marcos, who made the determinations. In this small collection there are specimens of the family Crotalidae,Elapidae and Colubridae. Among them there are specimens of solenoglipha, proteroglipha, opistoglipha and aglipha. We found the following species in the South.Orient: Bothrops castelnaudi (D. & B.), Lachesis muta (L.), Micrurus peruvianus, Micrurus hemprichii Jan, Xenodon severus (L.), Imantodes cenchoa (L.), Philodryas olfersii Lichtenstein, Oxybelis acuminatus Wied, Dipsa caterbyi Sentzen sp. and a specimen of the sub-family Rhadinea. Bothrops castelnaudi (D. & B.), has been found for the first time in Peru and with Lachesis Muta (L.), are the most dangerous snakes in that zone, it can be that they are responsible for almost every snake bite. It is confirmed that Madre de Dios is in the area of dispersion of Lachesis muta (L.), in Peru. Coral snakes are very common in this part of the jungle and the Micrurus peruvianus and Micrurus hemprihii Jan, has not been foud in Madre de Dios previously. Several specimens of Colubridae wich are not dangerous for men, were found in the South-Orient. Those are very common in the neighbor republic of Brazil.